Women in Peacekeeping Missions: Examining the Impact of Gender Participation on Defense Diplomacy and Confidence-Building in the ASEAN Region - Pamungkas, Maria Anatasya Sekar; Perwita, Anak Agung Banyu; Hendarwoto, Yermia (International Journal of Education, Culture, and Society, 2025)
This study examines the expanding role of women in peacekeeping operations within the ASEAN region and their contributions to defense diplomacy and confidence-building measures (CBMs). Situated within the global Women, Peace and Security (WPS) agenda, the integration of gender perspectives in peacekeeping enhances the legitimacy, effectiveness, and sustainability of missions. Anchored in feminist security theory and the defense diplomacy framework, the research analyzes empirical evidence from Indonesia, the Philippines, and Cambodia—three ASEAN member states that have increased female deployment in UN and regional peacekeeping initiatives. Employing qualitative case studies and policy document analysis, the findings demonstrate that female peacekeepers strengthen defense diplomacy by fostering interpersonal engagement, cross-cultural communication, and community-level trust-building. They positively influence local perceptions of security forces, improve access to vulnerable populations, and support post-conflict reconstruction and reconciliation processes. Nevertheless, persistent institutional and cultural barriers, including tokenism, limited leadership opportunities, and inadequate gender-sensitive training, constrain the full potential of women’s participation. The study concludes that mainstreaming gender perspectives in defense institutions, expanding capacity-building initiatives, and promoting regionally coherent ASEAN policies for inclusive peacekeeping are essential steps forward. The findings affirm that meaningful participation of women in peacekeeping is both a moral imperative and a strategic necessity for advancing regional peace, stability, and cooperation.